English Language Learning Strategies: The Case of Indonesian Monolinguals vs. Bilinguals - Hanif Maulaniam Sholah (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2019)
This research is aimed to investigate the different strategies of learning English language on monolingual and Bilingual learners. The goal of this research is to know whether the learners who speak one language in their daily life have different learning strategy compared with those who speak more than one language in their daily life. The population of the respondents are 300 university learners who study in semester 1 Kanjuruhan University of Malang, then 100 learners which consist of 50 Bilingual learners and 50 Monolingual learners are taken randomly as the subject of the research. Monolingual learners are those who speak one language only in their daily life, either Javanese or Indonesian or Madurish only. While bilingual learners are those who speaks two or more languages in their daily life communication. In selecting the respondents, researcher consider the homogeneity of the subject in the aspect of gender, age, nation and English speaking skill. The instrument used to collect the data in this research is language use instrument to determine the respondent then SILL questionnaires to collect the information about the use of language strategy. Oral interview is also be conducted to investigate the response more deeply as well as to crosscheck the respondents answers on their questionnaires in order to get the reliable data. To analyze the data, researcher used descriptive statistics and independent t-test using software SPSS Windows version. The result of analysis shows that there is no different language strategy significantly used by monolingual and Bilingual learners on the aspect of social, determination, memory, cognitive and metacognitive strategies. On the analysis of five category on English language learning strategy, Bilingual learners show that they use language learning strategy more respectively compared to monolingual learners. Bilingual learners more often use cognitive and memory strategies while Monolingual learners show that they prefer to use metacognitive and determination strategies.